Chest pain after percutaneous coronary intervention in patients with stable angina - Chang CC (Dove Medical Press, 2016)
Chao-Chien Chang,1–3 Yueh-Chung Chen,4,5 Eng-Thiam Ong,1 Wei-Cheng Chen,1 Chia-Hsiu Chang,1 Kuan-Jen Chen,1 Cheng-Wen Chiang1 1Division of Cardiology, Department of Internal Medicine, Cathay General Hospital, Taipei, Taiwan, ROC; 2Graduate Institute of Medical Sciences, Taipei Medical University, Taipei, Taiwan, ROC; 3Department of Pharmacology, Taipei Medical University, Taipei, Taiwan, ROC; 4Division of Cardiology, Department of Internal Medicine, Taipei City Hospital Ren-Ai branch, Taipai, Taiwan, ROC; 5Graduate Institute of Medical Sciences, National Defense Medical Center, Taipei, Taiwan, ROC Background: Percutaneous coronary intervention (PCI) has been widely used to treat acute coronary syndrome but is only recommended as an additional treatment to medical therapy and risk modification in patients with refractory or progressing angina. The number of PCI in this patient population is still increasing. Post-PCI chest pain (PPCP) is one of the common problems of PCI. Its presentation and causes in patients with stable angina are poorly understood.Patients and methods: This study retrospectively collected clinical information of 167 patients who had stable angina and underwent elective PCI, including 70 patients with PPCP 24 hours after procedure and 97 patients without PPCP. The incidence and predictors of PPCP were analyzed.Results: The incidence of PPCP was 41.9% (70/167). Compared with non-PPCP patients, PPCP patients had more abnormal post-PCI electrocardiogram (ECG) changes (new Q-waves, ST-segment shifts, or T-waves inversion) and serum cardiac troponin I (cTnI) elevation, more PCI vessels, and stent placement (all P<0.05). More PPCP patients required repeat revascularization than non-PPCP patients after PCI (P=0.043). PPCP was correlated with abnormal post-PCI ECG changes (P<0.0001), cTnI elevation (P<0.0001), post-PCI serum level of cTnI (P<0.0001), number of stents placed (P=0.009), and pre-PCI cTnI level (P=0.049). The strongest predictors of PPCP were abnormal post-PCI ECG changes (P<0.0001), post-PCI cTnI level (P<0.0001), and cTnI elevation (P<0.0001), followed by the number of stents placed (P=0.048).Conclusion: PPCP is common in patients with stable angina in our cohort. It is associated with abnormal ECG changes, cTnI elevation, and number of stents placed. Keywords: coronary angiography, percutaneous coronary interventions, chest pain, complications, interventional cardiology, cardiac troponin I